Effects of anti-Müllerian hormone and follicle stimulating hormone levels on in vitro fertilization pregnancy rate - Yi-Pin Chen; Wen-Hsiang Wu; Hsien-Ming Wu; Chun-Kai Chen; Hsin-Shih Wang; Hong-Yuan Huang (Elsevier, 2014)
Objectives: To analyze the relationship between in vitro fertilization (IVF) pregnancy rate and basal serum hormone levels before patients begin an IVF course. Materials and methods: In this retrospective study, we analyzed patients with anti-Müllerian hormone (AMH) data and IVF data from January 2009 to October 2012. Pregnancy rates were calculated by AMH and follicle stimulating hormone quartiles and analyzed using the independent samples t test. Furthermore, patients were divided into three groups by age. The Chi-square test was used to assess the association between the parameters and IVF pregnancy rates. Results: From the 910 IVF treatment courses, 377 (41.4%) clinical pregnancies resulted. The pregnant and nonpregnant groups differed significantly in age and FSH and AMH levels. The pregnancy rate was 53.3% for patients aged <32 years and 22.1% for patients aged >38 years. The pregnancy rate was 53.4% for patients with FSH levels <5.6 mIU/mL and 25.8% for patients with FSH levels >8.9 mIU/mL. The pregnancy rate was 56.8% for patients with AMH levels >4.0 ng/mL and 20.0% for patients with AMH levels <1.1 ng/mL. Furthermore, among patients aged <40 years, AMH and FSH were significantly associated with pregnancy rate. Higher pregnancy rates were found among the groups with higher AMH levels than in groups with lower AMH levels. Conclusion: For patients aged <40 years, basal serum AMH level and FSH level affected the IVF pregnancy rate, and patients with higher AMH levels had better pregnancy rates.